2010
DOI: 10.1155/2010/526934
|View full text |Cite
|
Sign up to set email alerts
|

Casting Activity ofScherotheca gigasin No-Till Mediterranean Soils: Role in Organic Matter Incorporation and Influence of Aridity

Abstract: The behaviour of earthworms, their role in organic matter incorporation into the soil, and the influence of aridity in such processes in arid and semiarid regions have scarcely been studied. In this study, physico-chemical analyses of the casts and the surrounding no-till agricultural soils of three experimental sites representing an aridity gradient in Navarre (NW Spain) were done. The casts were formed by the activity of the only anecic species, Scherotheca gigas (Dugès, 1828), ubiquitous in no-till soils in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Earthworms were collected in May as the barley reached physiological maturity by crumbling the 20 × 20 × 20 cm soil blocks by hand, placing the worms in a glass jar, and weighing to obtain a fresh weight for each treatment [68]. Previous studies determined that Scherotheca gigas (Dugés 1828) is the predominant anecic species in the area [69]. Microbial biomass carbon (MBC) was measured by comparing extractable C from non-fumigated and chloroform (CHCl 3 )-fumigated soil [70].…”
Section: Organic Matter and Soil Biological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Earthworms were collected in May as the barley reached physiological maturity by crumbling the 20 × 20 × 20 cm soil blocks by hand, placing the worms in a glass jar, and weighing to obtain a fresh weight for each treatment [68]. Previous studies determined that Scherotheca gigas (Dugés 1828) is the predominant anecic species in the area [69]. Microbial biomass carbon (MBC) was measured by comparing extractable C from non-fumigated and chloroform (CHCl 3 )-fumigated soil [70].…”
Section: Organic Matter and Soil Biological Propertiesmentioning
confidence: 99%
“…Only those variables for which the F statistic for soil management was significant (p < 0.05) were retained for further analysis. Earthworm biomass was included as an indicator because previous studies in this field had shown a direct relationship between earthworm activity and surface residue [69]. Factor analysis was then used to group the retained variables based on their correlation structure.…”
Section: Selection Of Soil Quality Indicatorsmentioning
confidence: 99%
“…A better understanding on the relationship between earthworms and soil management in calcareous soils like the one studied here is needed. In the region, it has been observed that earthworms can be positively affected by the reduction of tillage, and the concomitant gains in SOC in long-term trials [55,92,107]. Our results suggest that, when conventional tillage is used, fertilization may become a major driver of earthworm abundance in this type of soil.…”
Section: Soil Quality Assessmentmentioning
confidence: 65%
“…Earthworm indicators were, however, clearly sensitive to treatments in our study. Their response to soil and organic management has been widely studied, and reported in the sub-humid and semi-arid areas of the region [55,92,93]. In contrast, at the 15-30 cm depth, MBC was found to be significantly sensitive to treatments (Table 3).…”
Section: Sensitivity To Managementmentioning
confidence: 99%
“…Earthworm bioturbation, particularly cast production, has rarely been measured under NT (e.g., Bescansa, Virto, Fernández‐Ugalde, Imaz, & Enrique, 2010; Bottinelli, Hallaire, Menasseri‐Aubry, Le Guillou, & Cluzeau, 2019; Kaneda, Nakajima, Urashima, & Murakami, 2014), and although surface casting rates may achieve up to 3 Mg of soil ha −1 yr −1 in temperate NT fields in Japan (Miura et al, 2008) and 68–112 g m −2 d −1 (2.5–4.1 Mg ha −1 yr −1 ) in Nigerian NT fields (Lal & Akinremi, 1983), similar measurements have not been performed in Brazilian NT systems (despite visual observations of the phenomenon; Figures 2b,c). Surface casts represent a variable proportion of earthworm casting, depending on the species present and soil conditions, particularly moisture, temperature, food supply and bulk density (Barley, 1952; Joschko, Diestel, & Larink, 1989; Scullion & Ramshaw, 1988; Whalen, Sampedro, & Waheed, 2004).…”
Section: Functional Roles Of Earthworms In Brazilian Nt Systemsmentioning
confidence: 99%